Integrated three-dimensional computer-aided design and discrete-event simulation models - Xu, Jianfei; AbouRizk, S M; Fraser, Cam (Canadian journal of civil engineering, 2003)
Three-dimensional computer-aided design (3D-CAD) systems that integrate critical path method (CPM) algorithms, commonly referred to as four-dimensional computer-aided design (4D-CAD), have received a high level of interest over the past few years due to the insight they offer into constructability and feasibility analysis. This paper outlines an approach that facilitates this modeling method through integration between a commercial 3D-CAD software package and a discrete-event simulation tool. This approach employs a product-based modeling method that integrates simulation models with CAD drawings to provide real-time analysis and improved model accuracy in modeling construction operations. By integrating with 3D-CAD drawings, the models require much less data entry and provide a much higher degree of accuracy. Additionally, during the course of a project, resource and time consumption data can be collected and used to continually update the model, minimizing the use of assumptions and generalized data. This paper provides a short background and literature review to contextualize the problem statement, describes the product atomic component (PAC) used to integrate 3D-CAD and the simulation model, outlines some of the implementation issues in a simulation context, and presents a prototype system with an example application for an earthmoving project.Key words: 4D-CAD, CPM, product atomic component, simulation modeling, integration, earthmoving.